Understanding Shoppers’ Decision-Making Process in Traditional Markets in Indonesia - Widiyani; Ciadi, Yoke Mulyono; Putra, Bramana Ajasmara (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Every country has its own traditional place for trading fresh food known as the “marketplace.” In Indonesia, people refer to the marketplace as “traditional market.” Traditional markets encompass a variety of activities, such as buying and selling as well as social interactions and cultural features in rural and urban areas. Traditional markets are important for providing fresh produce to the local community and are mostly located close to residential areas. However, Indonesian traditional markets have experienced a decline due to the growth of modern markets, prompting the government to focus on attracting tourists to the traditional markets. Unfortunately, there are limited studies to determine if tourists represent an appropriate target market. The goal of this research was to enhance the understanding of traditional markets’ functions and factors that impact shoppers’ decisions to shop at traditional markets in Indonesia. Data from 506 respondents was collected through an online survey and a quantitative analysis was conducted. The results showed that regular customers are attracted to traditional markets by low prices and that they do not prioritize cleanliness, as these individuals are primarily interested in buying fresh produce. The study further suggests that customers in Indonesian traditional markets tend to display utilitarian behavior. As a result, stakeholders should consider traditional markets’ primary function as a place to purchase essential food items. While traditional markets can attract tourists, it is crucial to prioritize the preferences of the local community.